Visibility and Resolution Enhancement of Fourth-Order Ghost Interference with Thermal Light. (14th January 2015) - Wen, Feng; Zhang, Xun; Yuan, Chen-Zhi; Li, Chang-Biao; Wang, Jing-Da; Zhang, Yan-Peng
Abstract: A scheme for fourth-order double-slit ghost interference with a pseudo-thermal light source is proposed. It is shown that not only can the visibility be dramatically enhanced compared to the third-order case, but also higher resolution is demonstrated if we scan two of three reference detectors in opposite directions with the same speed, meanwhile another two in identical directions where the speed of one reference detector is twice the other. The results show that the visibility and resolution improvement of the fourth-order ghost interference fringe can be applied to the N th-order ghost imaging.